The Relationship Between Discipline in Islamic Religious Education and the Formation of Students' Moral Character - Nur Wahyuni (PT. Anagata Sembagi Education, 2026)
This study aims to determine the relationship between discipline in Islamic Religious Education (PAI) and the formation of moral character of students at the State Islamic Senior High School (MAN) in Surabaya. Discipline in PAI includes not only aspects of obedience in worship, but also compliance with school rules and consistency in practicing Islamic teachings in daily life. This study uses a quantitative approach with a correlational research type, involving 320 students from five of the best MAN in Surabaya as a sample, who were selected proportionally through a stratified random sampling technique. The instrument used consists of two Likert scales that measure the variables of PAI discipline and students' moral character. The results of the Pearson correlation test show a significant positive relationship between discipline in PAI and the formation of students' moral character with a correlation coefficient value of r = 0.673 (p < 0.01), which indicates a strong relationship. The dimension of obedience in worship has the highest correlation with moral character (r = 0.641), while the aspect of honesty is an indicator of moral character that is most strongly influenced by PAI discipline (r = 0.634). This study provides empirical evidence that the implementation of religious discipline integrated with Islamic Religious Education (PAI) learning practices contributes significantly to student character development, particularly in areas of honesty, responsibility, tolerance, and empathy. These findings underscore the importance of strengthening PAI as a vehicle for moral character development within the context of Islamic education in madrasas, through a habituation approach, role modeling, and the integration of values ​​into the school culture